(x+7)(x+7)=-14

Simple and best practice solution for (x+7)(x+7)=-14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x+7)(x+7)=-14 equation:


Simplifying
(x + 7)(x + 7) = -14

Reorder the terms:
(7 + x)(x + 7) = -14

Reorder the terms:
(7 + x)(7 + x) = -14

Multiply (7 + x) * (7 + x)
(7(7 + x) + x(7 + x)) = -14
((7 * 7 + x * 7) + x(7 + x)) = -14
((49 + 7x) + x(7 + x)) = -14
(49 + 7x + (7 * x + x * x)) = -14
(49 + 7x + (7x + x2)) = -14

Combine like terms: 7x + 7x = 14x
(49 + 14x + x2) = -14

Solving
49 + 14x + x2 = -14

Solving for variable 'x'.

Reorder the terms:
49 + 14 + 14x + x2 = -14 + 14

Combine like terms: 49 + 14 = 63
63 + 14x + x2 = -14 + 14

Combine like terms: -14 + 14 = 0
63 + 14x + x2 = 0

Begin completing the square.

Move the constant term to the right:

Add '-63' to each side of the equation.
63 + 14x + -63 + x2 = 0 + -63

Reorder the terms:
63 + -63 + 14x + x2 = 0 + -63

Combine like terms: 63 + -63 = 0
0 + 14x + x2 = 0 + -63
14x + x2 = 0 + -63

Combine like terms: 0 + -63 = -63
14x + x2 = -63

The x term is 14x.  Take half its coefficient (7).
Square it (49) and add it to both sides.

Add '49' to each side of the equation.
14x + 49 + x2 = -63 + 49

Reorder the terms:
49 + 14x + x2 = -63 + 49

Combine like terms: -63 + 49 = -14
49 + 14x + x2 = -14

Factor a perfect square on the left side:
(x + 7)(x + 7) = -14

Can't calculate square root of the right side.

The solution to this equation could not be determined.

See similar equations:

| 16.40=x-0.20*x | | 0.5P-10=50-P | | -8-7(r-6)=90 | | d=5m | | 2+5x=6x-8 | | 17x+11=180 | | 18x+4=180 | | x-8=2x-14 | | 16.40=x-020*x | | 1/3x35x7 | | 3x-(6x-4)/2=-2 | | -2.5-3y=-3 | | 9n^2-18n-16=0 | | 5x-2x-2=3x-9 | | 13+11x=360 | | 684=0.14x+0.10(1800+x) | | 11=1-2x | | 0.3x-0.5=0.2x+6 | | a^2-26=0 | | -6*3b+3+19b-6=0 | | 0=2x^2-8x | | 13+11x=180 | | Log^2(x+3)=4 | | 31/2r=28 | | 11x-4=360 | | -4x-11=2(x-3x)+13 | | x+0.10(600-x)=.55(600) | | 13.2=t-4.4 | | 0=-16t^2+38 | | 3n^2-n-14=0 | | 3(7x+4)=21x+21 | | 4m-12=12-2m |

Equations solver categories